Teacher-Facilitators' Job-Crafting: Making Meaning and Relevance in Authentic Learning Environments - Irma Kunnari; Vesa Tuomela; Jari Jussila (International School for Social and Business Studies, 2021)
Purpose: Higher education institutions are being challenged to sustain their relevance in a disruptive world by moving from ego-systems to ecosystems. Teachers, as key actors, are required to redesign their work, shifting from traditional teacher-led processes towards the facilitation of student-driven learning in authentic environments. In ecosystems, with students, colleagues, and work-life partners, teachers need to modify their work by crafting their tasks, relationships, and mindsets. This study aims to make the change in teachers' work transparent on a practical level. Study design/methodology/approach: A qualitative and practice-based approach was used to explore teacher facilitators experiences of their job crafting. Findings: The findings reveal the new meaning and relevance of the teacher facilitators work and can raise the awareness of higher education institutions to cultivate the future competencies of teachers. Originality/value: The study introduces the new nature and purpose of teachers' work as a part of ecosystems. We suggest higher education institutions nurture an experimental learning culture and support teachers to go out of their comfort zones. Developing collaborative job crafting can be a sustainable way to do that and avoids the disconnection between what we are doing and what we should be doing.